Learning from Gal Oya : possibilities for participatory development and post-newtonian social science - "Uphoff, Norman" (London, 1992)
This book recounts the drama of a remarkably successful experiment that introduced farmer organization for self-managed development in the largest and most run-down conflict-ridden irrigation system in Sri Lanka.
Keywords: Participatory development